2008
DOI: 10.1186/1471-2407-8-357
|View full text |Cite|
|
Sign up to set email alerts
|

Association of the germline TP53R337H mutation with breast cancer in southern Brazil

Abstract: Background: The germline TP53-R337H mutation is strongly associated with pediatric adrenocortical tumors (ACT) in southern Brazil; it has low penetrance and limited tissue specificity in most families and therefore is not associated with Li-Fraumeni syndrome. However, other tumor types, mainly breast cancer, have been observed in carriers of several unrelated kindreds, raising the possibility that the R337H mutation may also contribute to breast tumorigenesis in a genetic background-specific context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 27 publications
6
33
1
Order By: Relevance
“…This result falls within the range of that found in previous studies conducted in southern Brazil (2.4-13%) [17,18]. However, the study by Achatz et al is based on LFS/LFL families with tumors other than breast cancer.…”
Section: Discussionsupporting
confidence: 86%
“…This result falls within the range of that found in previous studies conducted in southern Brazil (2.4-13%) [17,18]. However, the study by Achatz et al is based on LFS/LFL families with tumors other than breast cancer.…”
Section: Discussionsupporting
confidence: 86%
“…[70-72] However, more recent studies have found that the R337H mutation can be found in families with a broad spectrum of LFS-associated cancers. [73, 74] …”
Section: Li-fraumeni Syndrome Core Cancersmentioning
confidence: 99%
“…In case of its mutation, this regulation could be lost, resulting in cell proliferation without control and development of cancer. TP53 mutation has been reported to have an association with risks of several cancers such as lung cancer [12], breast cancer [13], and colorectal cancer [14]. The loss of TP53 gene could damage its DNA-binding properties and transcription factor function, thus leading to aberrant cell proliferation.…”
Section: Introductionmentioning
confidence: 99%